2017
DOI: 10.1021/acs.jpcb.7b01309
|View full text |Cite
|
Sign up to set email alerts
|

Protic Ionic Liquids for the Belousov–Zhabotinsky Reaction: Aspects of the BZ Reaction in Protic Ionic Liquids and Its Use for the Autonomous Coil–Globule Oscillation of a Linear Polymer

Abstract: Herein, we describe the physicochemical aspects of the Belousov-Zhabotinsky (BZ) reaction in hydrated protic ionic liquids (PILs) combined with different cations with a hydrogen sulfate ([HSO]) anion. PILs were prepared from the neutralization reactions of sulfuric acid with 13 different aliphatic amines. The amine structure was selected to investigate the effect of the number of active protons, alkyl chain length (hydrophilicity), and cationic linearity on the mechanism of the BZ reaction. The pK values of PI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…[14,15] Moreover,P ILs having high proton activity (comparable to as trongly acidic aqueous solution) can be developed as proton conducting media for non-humidified fuel cell membrane applications. [17,18] TheB Zr eaction proceeds with the slow oxidation of an organic substrate (for example malonic acid (MA)) by an oxidant (such as sodium bromate) in the presence of ametal catalyst (for example Ru(bpy) 3 )and protons.Importantly,the redox state of the metal catalyst changes periodically during the reaction. [17,18] TheB Zr eaction proceeds with the slow oxidation of an organic substrate (for example malonic acid (MA)) by an oxidant (such as sodium bromate) in the presence of ametal catalyst (for example Ru(bpy) 3 )and protons.Importantly,the redox state of the metal catalyst changes periodically during the reaction.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…[14,15] Moreover,P ILs having high proton activity (comparable to as trongly acidic aqueous solution) can be developed as proton conducting media for non-humidified fuel cell membrane applications. [17,18] TheB Zr eaction proceeds with the slow oxidation of an organic substrate (for example malonic acid (MA)) by an oxidant (such as sodium bromate) in the presence of ametal catalyst (for example Ru(bpy) 3 )and protons.Importantly,the redox state of the metal catalyst changes periodically during the reaction. [17,18] TheB Zr eaction proceeds with the slow oxidation of an organic substrate (for example malonic acid (MA)) by an oxidant (such as sodium bromate) in the presence of ametal catalyst (for example Ru(bpy) 3 )and protons.Importantly,the redox state of the metal catalyst changes periodically during the reaction.…”
mentioning
confidence: 99%
“…[18] When PILs having longer alkyl chains are used, hydrophobic interaction between the alkyl chain and Ru(bpy) 3 redox center seems to inhibit effective electron transfer,resulting in unstable oscillation. Our previous report revealed that stable redox oscillation of Ru(bpy) 3 during the BZ reaction could be achieved by using PILs possessing short alkyl chains in the cation structure.…”
mentioning
confidence: 99%
See 3 more Smart Citations